MONEY SUPPLY AND BANK RESERVES POLICY OF THE CENTRAL BANK: ANALYSIS IN THE WORLD AND UZBEKISTAN (Marketing Journal, 2025)
This article presents a scientific analysis of central bank policies on money supply and bank reserves, comparing international experience with Uzbekistan’s monetary practices. The study examines the relationship between the money supply (aggregates M1, M2, M3) and reserve requirements, as well as their impact on economic growth, inflation, and financial stability. The experiences of major central banks such as the U.S. Federal Reserve System, the European Central Bank, and the Bank of Japan are compared with the monetary policy of the Central Bank of the Republic of Uzbekistan. The findings reveal that in recent years Uzbekistan has gradually reduced reserve ratios and expanded the money supply to stimulate economic growth; however, this has also intensified inflationary pressures and affected the quality of banking assets. The author proposes scientifically grounded recommendations to optimize monetary policy, integrate risk-based reserve management mechanisms, and adapt global best practices to the national economy.
Keywords: money supply; bank reserves; central bank; monetary policy; inflation; liquidity; financial stability; Uzbekistan